A study on heat treatment of carburizing carbon steel - Mohd Marhan, Asari (2010)
The main purpose of this study is to study the effect of heat treatment of carburizing carbon steel by using three parameters (carburizing hour, carburizing temperature, and quenching medium). This study was conducted using a furnace. This process is carried out at temperatures from 850°C to 950°C (1123 – 1223K) for three various duration time which are 8, 10 and 12 hours. From the experiment, the thickness of carbon layer varied according to the parameters that been used. For carburizing temperature at 950°C, the thickness of carbon layer was between 40μm to 80μm for oil as quenching medium, 60μm to 100μm for water as quenching medium and 20μm to 60μm for air as quenching medium. This experiment also been conducted for different carburizing temperature but with one quenching medium which is oil. The thickness of carbon layer was between 20μm to 60μm for 850°C, 30μm to 70μm for 900°C and 40μm to 80μm for 950°C. For carburizing temperature at 950°C, surface hardness values of carburized specimens were between 185.9HV and 386.2HV for oil as quenching medium, 234.7 HV and 398.4HV for water as quenching medium and 120.7HV and 241.5HV for air as quenching medium. For different carburizing temperature, surface hardness values of carburized specimens were between 149 HV and 323.4HV for 850°C, 166.4 HV and 345.9HV for 900°C and 185.9HV and 368.2HV for 950°C. Activation energy was determined by 47.34kJ/mol. The lower value of activation energy means less energy required for carbon atoms to diffuse into carbon steel, thus provide a more effective and efficient process.